Hard coating composition and preparation method thereof
By forming a polymer coating layer on the surface of silver nanoparticles and adding an alkaline dispersant to the hard coating composition, the problem of degradation of antibacterial properties caused by agglomeration of silver nanoparticles is solved, and silver in the hard coating composition is realized Good dispersion and efficient antibacterial properties of nanoparticles.
Patent Information
- Application Number
- CN202380049849.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-27
- Filing Date
- 2023-06-23
- Publication Date
- 2025-02-14
AI Technical Summary
In the conventional hard coating composition, silver nanoparticles are prone to agglomeration, resulting in a decrease in antibacterial properties and making it difficult to maintain good dispersion in the coating.
By forming a polymer cladding layer on the surface of the silver nanoparticles and adding an alkaline dispersant to the hard coating composition, the silver nanoparticles are prevented from agglomerating and ensuring good dispersion.
The excellent dispersion and antibacterial properties of silver nanoparticles in the hard coating composition were achieved, ensuring that the bactericidal effect of the coating on Staphylococcus aureus and E. coli reached more than 99.9%.
Smart Images

Figure CN119452048A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a hard coating composition, and more particularly to a hard coating composition with excellent antibacterial properties and a preparation method thereof. Background Art
[0002] Hard coating is a surface protection technology widely used in various plastic products such as building materials, automotive exterior parts, furniture and display panels.
[0003] In recent years, in addition to surface protection and scratch prevention, there has been an increasing demand for hard coating compositions with antibacterial properties because products that frequently come into contact with human hands, such as various home appliances, tablets, or smartphones, may transmit bacteria through the users' hands and cause harm.
[0004] On the other hand, silver nanoparticles (AgNP) are known to have antibacterial and bactericidal effects and have been used in various fields such as coatings, electronic components, catalysts, and biomaterials in recent years, and methods for applying them to various products that come into contact with the human body are being developed. Summary of the invention
[0005] Technical issues to be solved
[0006] The object of the present invention is to provide a hard coating composition containing silver nanoparticles having antibacterial and bactericidal effects, wherein the silver nanoparticles do not agglomerate in the hard coating composition and have excellent dispersibility and antibacterial properties.
[0007] Technical Solution
[0008] According to one aspect of the present invention, the antimicrobial hard coating composition is characterized by comprising:
[0009] Silver nanoparticles having a coating layer formed of a polymer on the surface and containing 0.02 to 0.2 weight % of the weight of the antibacterial hard coating composition;
[0010] Adhesive resin;
[0011] a curing agent for curing the adhesive resin;
[0012] an organic solvent for dissolving the binder resin and comprising a ketone solvent; and
[0013] A basic dispersant for dispersing the silver nanoparticles.
[0014] Among them, it is preferred that the antibacterial performance of the hard coating composition against Staphylococcus aureus and Escherichia coli after curing is 99.9% or more.
[0015] In addition, the alkaline dispersant is preferably one or more selected from the group consisting of sodium hydroxide, diethanolamine, triethanolamine, and phosphine ligand-substituted substances.
[0016] In addition, the alkaline dispersant is preferably contained in an amount of 5 to 20 parts by weight based on 100 parts by weight of the silver nanoparticles.
[0017] In addition, the average particle size of the silver nanoparticles is preferably 5 to 50 nanometers.
[0018] In addition, the silver nanoparticles are preferably spherical.
[0019] In addition, the molecular weight of the capping agent is preferably 10,000 to 360,000.
[0020] In addition, the coating layer preferably has a thickness of 0.5 nm to 10 nm.
[0021] In addition, the ketone solvent is preferably methyl ethyl ketone.
[0022] According to another aspect of the present invention, it is characterized by comprising the following steps:
[0023] Preparation steps of silver nanoparticles: Ag is + Ion reduction forms a coating layer composed of a polymer on its surface to synthesize silver nanoparticles;
[0024] a dispersion preparation step of mixing the silver nanoparticles with methyl ethyl ketone;
[0025] The hard coating liquid preparation step is to mix the dispersion liquid with a binder resin and an alkaline dispersant so that the content of the silver nanoparticles is 0.02 to 0.2 weight % of the weight of the hard coating composition.
[0026] Beneficial Effects
[0027] The hard coating composition according to the present invention can be widely used in various applications such as elevators, handles, tables, etc. through coating, and can be mainly used as a coating material for transparent displays. It is characterized by containing silver nanoparticles and having excellent antibacterial and bactericidal effects.
[0028] In addition, by including an alkaline dispersant, the silver nanoparticles will not agglomerate but can be well dispersed, so that after the hard coating composition is applied to the plastic substrate for coating, the silver nanoparticles will still not agglomerate, and a high surface area per unit area can be maintained, which has an excellent antifouling effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1It is a schematic diagram showing the phenomenon that the silver nanoparticles applied in the hard coating liquid cannot combine with methyl ethyl ketone (MEK), the main solvent of the hard coating liquid, resulting in the distance between the silver nanoparticles becoming shorter and agglomeration occurring.
[0030] Figure 2 It is a schematic diagram used to illustrate the phenomenon that silver nanoparticles used in the hard coating liquid cannot be well dispersed in the hard coating liquid in an acidic environment and agglomerate.
[0031] Figure 3 It is a schematic diagram for explaining the phenomenon that the silver nanoparticles used in the hard coating liquid according to the present invention will not agglomerate but can be well dispersed in the hard coating liquid in an alkaline environment.
[0032] Figure 4 Schematic diagram showing a method for preparing a hard coating composition according to one aspect of the present invention. DETAILED DESCRIPTION
[0033] Before describing the present invention in detail, it should be understood that the terms used in this specification are only used to describe specific embodiments and are not limited only by the appended claims. Unless otherwise specified, all technical terms and scientific terms used in this specification have the same meaning as those commonly understood by those skilled in the art.
[0034] In addition, when interpreting the terms or words used in this specification and claims, they should not be limited to the usual or dictionary meanings, but should be interpreted in accordance with the meanings and concepts consistent with the technical ideas of the present invention in accordance with the content of this specification, based on the principle that the inventor appropriately defines the concepts of terms in order to best explain his invention.
[0035] Throughout this specification and claims, unless otherwise stated, the words “comprise”, “comprises” and “comprising” mean including a stated item, step or a group of items and steps, and do not exclude any other item, step or group of items or steps.
[0036] In addition, the various embodiments of the present invention can be combined with any other embodiments unless otherwise explicitly stated. In particular, any feature indicated as particularly preferred or advantageous can be combined with other features indicated as preferred or advantageous. The embodiments of the present invention and their effects are described below with reference to the accompanying drawings.
[0037] <First Aspect of the Invention>
[0038] According to a first aspect of the present invention, a hard coating composition containing silver nanoparticles is provided. The hard coating composition comprises silver nanoparticles, an alkaline dispersant, a binder resin and an organic solvent.
[0039] Silver nanoparticles are a material used to improve the antifouling ability of hard coating compositions, especially silver particles coated with a coating agent, which prevent the agglomeration of silver particles through electrostatic repulsion and steric hindrance, resulting in an increase in particle size and play a role in increasing dispersion stability.
[0040] The silver nanoparticles of the present invention are characterized in that + The ion surface is bound to a coating agent and has a coating layer.
[0041] The capping agent refers to a polymeric substance attached to the surface of the silver nanostructure to enable the surface of the silver nanoparticles to crystallize.
[0042] The coating agent may be a surface-attaching polymer such as polyvinylpyrrolidone (PVP), polyvinylalcohol (PVA), polyacrylamide (PAM) or polyacrylic acid (PAA), and PVP is preferably used.
[0043] At this time, the molecular weight of the coating agent is preferably 10,000 to 360,000. If the molecular weight of the coating agent is lower than 10,000, the formed polymer film is too thin and may not effectively prevent the problem of mutual agglomeration between silver nanoparticles; if the molecular weight of the coating agent exceeds 360,000, due to the long length of the polymer chain, it is difficult to attach to the surface of the silver precursor due to steric hindrance, and the silver nanoparticles cannot be well formed.
[0044] At this time, silver nanoparticles with an average particle size of 5 to 50 nanometers, preferably 20 to 40 nanometers, are used. If the average particle size of the silver nanoparticles is lower than the above range, the loss rate is large in the purification step after synthesis; if it exceeds the above range, the surface area of the silver nanoparticles exposed per unit area is smaller than that of the same solid content, and the antibacterial performance cannot be well demonstrated.
[0045] The coating agent is mixed in an amount of 1,000 to 10,000 parts by weight, preferably 3,000 to 5,000 parts by weight, based on 100 parts by weight of the silver precursor.
[0046] In addition, the thickness of the coating layer formed by PVP of the silver nanoparticles is 0.5 nm to 10 nm, preferably 1 nm to 6 nm.
[0047] The content of the silver nanoparticles is preferably 0.02 to 0.2 weight percent, more preferably 0.09 to 0.12 weight percent of the weight of the hard coating composition. If the content of the silver nanoparticles is lower than the above range, the surface area of the silver nanoparticles exposed per unit area is small, and the antibacterial performance may not be well demonstrated; if it exceeds the above range, the viscosity of the overall composition increases, resulting in decreased working performance, and decreased adhesion to the substrate after coating.
[0048] On the other hand, the method for preparing silver nanoparticles having a coating layer can typically use a polyol synthesis method among solution synthesis methods.
[0049] Polyol refers to alcohols containing more than two hydroxyl groups (-OH) in the molecule. The polyol synthesis method is a method of synthesizing silver nanostructures using such polyols, i.e., multivalent alcohols, as solvents and reducing agents.
[0050] Typically, a polymeric substance that acts as a growth control and protective film is added to the preheated polyol along with silver ions to induce a reduction reaction.
[0051] At this time, the polymer substance acts as a capping agent attached to the surface of the silver nanostructure, and forms a capping layer around the particle surface as the redox reaction in the solution, so that the synthesized silver nanoparticles can be maintained stably for a long time.
[0052] Polyvinylpyrrolidone (PVP) is a commonly used polymer in the synthesis of silver nanoparticles. PVP can simultaneously act as a reducing agent to reduce silver ions to silver nanoparticles and a stabilizer to stabilize the dispersion of synthesized silver nanoparticles.
[0053] For example, silver nanoparticles can be prepared by mixing an ethylene glycol (EG) solution in which silver nitrate (AgNO 3 ) is dissolved and an EG solution in which polyvinylpyrrolidone (PVP) is dissolved, and heating the mixture.
[0054] Since the silver nanoparticles prepared by the polyol synthesis method have a coating layer, in order to make them applied in the hard coating composition and exhibit antibacterial properties, an alkaline dispersant is added so that they do not agglomerate in the hard coating composition and can be well dispersed. Sodium hydroxide, diethanolamine, triethanolamine, phosphine ligand substituted substances, etc. can be used as the alkaline dispersant, and the content is preferably 0.005 to 0.05 parts by weight, more preferably 0.01 to 0.03 parts by weight relative to 100 parts by weight of the organic solvent.
[0055] The dispersibility of silver nanoparticles behaves differently depending on the solvent used, e.g. Figure 1 As shown, when silver nanoparticles with a PVP coating layer are dispersed in water or ethanol, they may exhibit dispersibility due to the electrostatic attraction between the oxygen atoms in the PVP molecules and the hydrogen atoms in the ethanol or water molecules.
[0056] However, unlike water and ethanol, PVP forming the silver nanoparticle coating layer cannot form electrostatic attraction with the methyl ethyl ketone (MEK) molecules, the main solvent of the hard coating liquid in the embodiment of the present invention, and therefore cannot be well dispersed and agglomerates, which may cause the particle size of the silver nanoparticles to increase, causing the silver nanoparticles to agglomerate and fail to achieve antibacterial properties.
[0057] In addition, the general hard coating liquid has a low pH acidity, such as Figure 2 As shown, the electrons around the silver nanoparticles interact with the hydrogen ions (H + ) causes the silver nanoparticles to agglomerate. When the hard coating liquid prepared in this way is evaluated for antibacterial properties after coating, it may not be able to exhibit good antibacterial properties due to the small surface area of silver nanoparticles exposed per unit area.
[0058] To this end, the dispersibility of the silver nanoparticles can be improved by adding the above-mentioned alkaline dispersant. Figure 3 It is a schematic diagram for explaining the phenomenon that the silver nanoparticles used in the hard coating liquid do not agglomerate but can be well dispersed in the hard coating liquid in an alkaline environment.
[0059] The adhesive resin may include acrylic, urethane or silicone resin (or monomer).
[0060] Specifically, the binder resin may include poly(meth)acrylic acid and its salts, poly(meth)acrylate, butyl ester, polyacrylamide, polyacrylonitrile, polyurethane, polyester, melamine, vinyl acetate, polyethylene, polypropylene, polyvinyl alcohol, polyethylene glycol, epoxy resin, siloxane, polydimethylsiloxane or copolymers thereof.
[0061] The content of the binder resin is preferably 50 to 100 parts by weight, more preferably 60 to 80 parts by weight, based on 100 parts by weight of the organic solvent.
[0062] In addition, the hard coating composition may further include a curing agent for curing the above-mentioned adhesive resin. The material of the curing agent is not limited, and specifically, aliphatic amines such as diethylenetriamine and triethylenetetramine, aromatic amines such as m-phenylenediamine, diaminodiphenylmethane, diaminodiphenylsulfone, and azomethylphenol, polyvalent hydroxy compounds such as phenolic resin, o-cresol resin, naphthol resin, phenol aralkyl resin, and modified products thereof, anhydride curing agents such as phthalic anhydride, maleic anhydride, hexahydrophthalic anhydride, pyromellitic anhydride, dicyandiamide, imidazole, boron trifluoride-amine complex, and guanidine derivatives, etc., preferably, one or more of the above curing agents are selected and used in combination.
[0063] The content of the curing agent is preferably 5 to 10 parts by weight, more preferably 5 to 8 parts by weight, based on 100 parts by weight of the organic solvent.
[0064] The organic solvent is used to dissolve the above-mentioned binder resin and the like, and plays a role in adjusting the fluidity of the hard coating composition.
[0065] Specifically, the organic solvent can use alcohols such as methanol or isopropanol, ketones such as acetone, methyl ethyl ketone, methyl butyl ketone or methyl isobutyl ketone, ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethyl ether, dimethyl ether or propylene glycol ether, and methyl ethyl ketone is most preferably used to improve the adhesion of the hard coating film. In addition, the organic solvent in the present invention includes an organic solvent contained in the silver nanoparticle dispersion when preparing the silver nanoparticles.
[0066] The additives may include non-alkaline dispersants, plasticizers, anti-settling agents, defoamers, thickeners, anti-filming agents, etc. Non-alkaline dispersants may include block copolymers, sodium naphthalene sulfonate, sodium alkyl naphthalene sulfonate, sodium phenol sulfonate, alkyl diphenyl ether, polyoxyethylene alkyl ether, nonionic surfactants, sodium polyacrylate, olefin-sodium maleate, condensed phosphates, carboxymethyl cellulose, amine derivatives, etc. In order to improve the dispersibility of the hard coating composition, a block copolymer series dispersant may be used.
[0067] The non-alkaline dispersant is contained in an amount of preferably 0.005 to 0.05 parts by weight, more preferably 0.01 to 0.03 parts by weight, based on 100 parts by weight of the organic solvent.
[0068] In addition, the hard coating composition of the present invention is characterized in that the antibacterial performance against Staphylococcus aureus and Escherichia coli after curing is 99.9% or more.
[0069] <Second Aspect of the Invention>
[0070] According to a second aspect of the present invention, a method for preparing a hard coating composition is provided.
[0071] Figure 4Schematic diagram showing a method for preparing a hard coating composition according to one aspect of the present invention.
[0072] The method for preparing the hard coating composition comprises a step of preparing silver nanoparticles, a step of preparing a silver nanoparticle dispersion liquid and a step of preparing a hard coating liquid.
[0073] The silver nanoparticle preparation step includes a first solution preparation process of preparing a coating agent solution, a second solution preparation process of preparing a silver precursor solution, a synthesis process of mixing the first solution and the second solution to synthesize silver nanoparticles, and a purification process of purifying the silver nanoparticles.
[0074] The first solution preparation step is a step of dissolving the coating agent in a reducing solvent and heating the solvent to prepare a coating agent solution.
[0075] The capping agent refers to a polymeric substance attached to the surface of the silver nanostructure to enable the surface of the silver nanoparticles to crystallize.
[0076] The coating agent may be a surface-attaching polymer such as polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), polyacrylamide (PAM) or polyacrylic acid (PAA), and PVP is preferably used.
[0077] At this time, the molecular weight of the coating agent is preferably 10,000 to 360,000. If the molecular weight of the coating agent is lower than 10,000, the formed polymer film is too thin and may not effectively prevent the problem of mutual agglomeration between silver nanoparticles; if the molecular weight of the coating agent exceeds 360,000, due to the long length of the polymer chain, it is difficult to attach to the surface of the silver precursor due to steric hindrance, and the silver nanoparticles cannot be well formed.
[0078] The reducing solvent refers to a polar solvent that can dissolve the silver precursor and the coating agent, and contains at least two hydroxyl groups in the molecule. For example, solvents such as diols, polyols or ethylene glycol can be used.
[0079] Specifically, the reducing solvent includes ethylene glycol (EG), propylene glycol (PG) or glycerol, and more specifically may include at least one of ethylene glycol, polyethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, glycerol, glycerol and diethylene glycol. Preferably, one or more of ethylene glycol, polyethylene glycol or propylene glycol is used, and more preferably ethylene glycol is included.
[0080] At this time, the reducing solvent is preferably mixed in an amount of 0.5 to 5 times the weight of the coating agent.
[0081] In addition, the coating agent solution formed by mixing the coating agent and the reducing solvent is preferably heated and maintained at 130°C to 170°C.
[0082] According to one embodiment, a reducing solvent and a coating agent are put into a reactor, stirred and mixed using a stirrer, and heated to make the internal temperature of the reactor reach 140° C. to 170° C. to prepare a first solution.
[0083] The second solution preparation step is a step of dissolving a silver precursor in a reducing solvent to prepare a silver precursor solution.
[0084] The silver precursor is composed of silver ions (Ag + ) and an organic or inorganic anion, the organic or inorganic anion including [NO3] - ,[ClO4] - ,[BF4] - ,[PF6] - ,[CH3COO] - ,[CF3SO3] - ,[SO4] 2- ,[CH3COCH=COCH3] - And other organic or inorganic anions.
[0085] The silver precursor can be specifically selected from AgBF4, AgCF3SO3, AgClO4, AgNO3, Ag(CH3COO), AgPF6 or Ag(CF3COO), or a mixture thereof.
[0086] The reducing solvent used in the second solution preparation step can be the reducing solvent listed in the first solution preparation step, preferably including one or more of the reducing solvents used in the first solution preparation step. At this time, the reducing solvent acts as a reducing agent to reduce the silver precursor to form silver ions.
[0087] At this time, the reducing solvent is preferably mixed with 1 to 20 times the weight of the silver precursor.
[0088] In addition, the silver precursor solution formed by mixing the silver precursor and the reducing solvent is preferably stirred and maintained at a temperature of 10° C. to 30° C. for 3 hours or more.
[0089] The synthesis step is a step of mixing the coating agent solution and the silver precursor solution prepared in the first solution preparation step and the second solution preparation step to form a mixed solution, and synthesizing silver nanoparticles.
[0090] Here, the capping agent in the mixed solution surrounds and binds to the surface of the Ag+ ions reduced by the reducing solvent to form a film or a capping layer.
[0091] At this time, the formed silver nanoparticles preferably have a particle size of 5 to 50 nanometers, and the coating layer preferably has a thickness of 1 to 6 nanometers. At this time, the thickness of the coating layer can be estimated by removing the solvent and the polymer, assuming that the silver nanoparticles are completely spherical, calculating the volume and mass of the Ag particles, and then calculating the corresponding polymer mass and volume. That is, assuming that PVP is coated on Ag in a spherical manner, by reversely calculating the diameter of the coated portion.
[0092] In the synthesis step, the silver precursor can be mixed in the entire mixed solution at a concentration of 0.01mol / l to 1.0mol / l, or mixed at a concentration of 5g / kg to 100g / kg by weight. At this time, if the concentration is lower than 0.01mol / l or 5g / kg, the amount of nanoparticles generated is sharply reduced; if it exceeds 1.0mol / l or 100g / kg, the problem of nanoparticle aggregation is caused by excessive production. It is more preferably mixed at a concentration of 0.05mol / l to 0.5mol / l or 10g / kg to 30g / kg.
[0093] In addition, the coating agent is mixed in an amount of 1000 to 10000 parts by weight, preferably 3000 to 5000 parts by weight, relative to 100 parts by weight of the silver precursor. If the coating agent is below the above range, the diameter of the generated nanoparticles will increase; if it exceeds the above range, the coating layer thickness will increase and it will be difficult to show antibacterial properties.
[0094] The purification step is a step of cooling the nanoparticles after the reaction to room temperature, and washing and purifying them using acetone, ethanol, etc. to obtain synthesized silver nanoparticles.
[0095] At this time, the solvent and unreacted polymer of the silver nanoparticles are removed in the purification step, the volume and mass of the obtained silver nanoparticles are calculated, and then the corresponding polymer mass and volume are calculated. In addition, assuming that the silver nanoparticles form a perfect sphere and the PVP is coated on the silver particles in a spherical manner, the thickness of the coating layer can be calculated by reversely calculating the diameter of the coated silver particle portion.
[0096] The silver nanoparticle dispersion preparation step is a step of mixing the silver nanoparticles obtained in the silver nanoparticle preparation step with a dispersion solvent to prepare a dispersion.
[0097] The dispersion solvent may be distilled water, ethanol, isopropyl alcohol or the like, and it is preferable to use the same solvent as that used in the next step of preparing the hard coating liquid.
[0098] At this time, the silver nanoparticle dispersion preferably contains 5 to 25 parts by weight of silver nanoparticles in 100 parts by weight of the total, and more preferably contains 12 to 16 parts by weight.
[0099] The hard coating liquid preparation step is a step of mixing a binder resin, a silver nanoparticle dispersion liquid, and an alkaline dispersant to prepare a hard coating composition.
[0100] Specifically, after mixing the silver nanoparticle dispersion and the binder resin, an alkaline dispersant is added and dispersed by a shaker to prepare a hard coating composition.
[0101] At this time, the adhesive resin may include acrylic, urethane or silicone resin (or monomer).
[0102] The above-mentioned adhesive resin may include poly(meth)acrylic acid and its salt, poly(meth)acrylate, butyl ester, polyacrylamide, polyacrylonitrile, polyurethane, polyester, melamine, vinyl acetate, polyethylene, polypropylene, polyvinyl alcohol, polyethylene glycol, epoxy resin, siloxane, polydimethylsiloxane, or copolymers thereof.
[0103] In addition, the hard coating composition may further include a curing agent for curing the above-mentioned adhesive resin. The material of the curing agent is not limited, and specifically, aliphatic amines such as diethylenetriamine and triethylenetetramine, aromatic amines such as m-phenylenediamine, diaminodiphenylmethane, diaminodiphenylsulfone, and azomethylphenol, polyvalent hydroxy compounds such as phenolic resin, o-cresol resin, naphthol resin, phenol aralkyl resin, and modified products thereof, anhydride curing agents such as phthalic anhydride, maleic anhydride, hexahydrophthalic anhydride, pyromellitic anhydride, dicyandiamide, imidazole, boron trifluoride-amine complex, and guanidine derivatives, etc., preferably, one or more of the above curing agents are selected and used in combination.
[0104] The content of the curing agent is preferably 5 to 10 parts by weight, more preferably 5 to 8 parts by weight, based on 100 parts by weight of the organic solvent.
[0105] The organic solvent is used to dissolve the above-mentioned binder resin and the like, and plays a role in adjusting the fluidity of the hard coating composition.
[0106] Specifically, the organic solvent may include alcohols such as methanol, ethanol and isopropanol, ketones such as acetone, methyl ethyl ketone, methyl butyl ketone and methyl isobutyl ketone, and ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethyl ether, dimethyl ether and propylene glycol ether. In order to improve the adhesion of the hard coating film, methyl ethyl ketone is most preferably used.
[0107] The alkaline dispersant is a substance added to enable the PVP-coated silver nanoparticles to be well dispersed in the organic solvent of the hard coating composition, and at least one of sodium hydroxide, diethanolamine, triethanolamine, and phosphine ligand-substituted substances can be used.
[0108] The content of the basic dispersant is preferably 0.005 to 0.05 parts by weight, more preferably 0.01 to 0.03 parts by weight, based on 100 parts by weight of the organic solvent.
[0109] The additives serve to adjust the overall dispersibility of the silver nanoparticles and the hard coating composition.
[0110] Specifically, the additives may include non-alkaline dispersants, plasticizers, anti-settling agents, defoamers, thickeners, anti-filming agents, etc. In order to improve the dispersibility of the hard coating composition, non-alkaline dispersants are used. Non-alkaline dispersants may include block copolymers, sodium naphthalenesulfonate, sodium alkylnaphthalenesulfonate, sodium phenolsulfonate, alkyl diphenyl ether, polyoxyethylene alkyl ether, nonionic surfactants, sodium polyacrylate, olefin-sodium maleate, condensed phosphates, carboxymethyl cellulose, amine derivatives, etc. In order to improve the dispersibility of the hard coating composition, block copolymer series dispersants are used.
[0111] The non-alkaline dispersant is preferably contained in an amount of 0.005 to 0.05 parts by weight, more preferably 0.01 to 0.03 parts by weight, relative to 100 parts by weight of the organic solvent. In addition, when a non-alkaline dispersant is included, the alkaline dispersant and the non-alkaline dispersant are preferably used in a ratio of 1:0.8 to 1:1.
[0112] The hard coating composition prepared according to the hard coating liquid preparation step of the present invention is characterized in that the pH is 2 to 6, preferably 2.5 to 5.5 at 25°C. If the pH is lower than 2, the silver nanoparticles cannot be well dispersed in the hard coating composition, the distance between the silver nanoparticles becomes shorter and agglomerates, resulting in the problem of increased particle size of the silver nanoparticles.
[0113] <Examples and Comparative Examples>
[0114] Preparation of hard coating compositions
[0115] <Example 1>
[0116] 700 g of polyethylene glycol (molecular weight of about 400 g / mol) and 500 g of ethylene glycol were added into a double-jacketed reactor and stirred thoroughly, and then 30 g of PVP (polyvinyl pyrrolidone, molecular weight of about 10,000 g / mol) was added and stirred thoroughly. A circulator was used to heat until the internal temperature of the reactor stabilized at 150°C to prepare a first solution.
[0117] In another reactor, 50 g of ethylene glycol solvent was prepared, and 15 g of silver nitrate was added and stirred to dissolve for more than 3 hours to prepare a second solution.
[0118] The second solution was added to the first solution to prepare a mixed solution, which was stirred for 5 minutes to synthesize silver nanoparticles with surfaces coated with PVP.
[0119] The mixed solution was then cooled to room temperature and purified to obtain silver nanoparticles. The purification process was to add acetone equivalent to 3 times or more of the volume of the mixed solution to the silver nanoparticles, and then use centrifugal separation to precipitate them, remove the supernatant containing unreacted polymers and synthesis residues, and obtain the precipitate, that is, the purified PVP-coated silver nanoparticles.
[0120] At this time, the target polymer content can be achieved by performing the purification process three times, and 7.0 g of silver nanoparticles having an average particle size of 35 nm and an average coating layer thickness of 5 nm formed by the polymer are obtained.
[0121] Furthermore, after measuring the content of the silver nanoparticles, a 15% dispersion was prepared using ethanol to prepare a silver nanoparticle dispersion for a hard coating composition.
[0122] Then, 1.0 g of the obtained 15% silver nanoparticle dispersion, 0.015 g of diethanolamine as a basic dispersant, 56 g of poly(meth)acrylic acid, 5.6 g of a curing agent, and 87 g of methyl ethyl ketone were mixed to prepare a hard coating liquid.
[0123] <Examples 2 to 4>
[0124] The hard coating compositions of Examples 2 to 4 were prepared by the same preparation method as Example 1 using the preparation components and proportions in Table 1 and Table 2.
[0125] <Comparative Examples 1 to 2>
[0126] The hard coating compositions of Comparative Examples 1 to 2 were prepared by the same preparation method as Example 1 using the preparation components and proportions in Table 1 and Table 2.
[0127] [Table 1]:
[0128]
[0129] [Table 2]
[0130]
[0131] <Examples 5 to 8, Comparative Examples 3 to 4>
[0132] The coatings with antibacterial properties of Examples 5 to 8 and Comparative Examples 3 to 4 were coated on a PET substrate and then heated and cured at 100° C. to prepare a hard coating film.
[0133] <Test example>
[0134] <Test Example 1: Antibacterial Test>
[0135] In order to evaluate the antibacterial properties of the films of Examples 5 to 8 and Comparative Examples 3 to 4, the "film lamination method JIS Z 2801" was used for evaluation. The above films were made into 5 cm × 5 cm samples, a certain amount of liquid bacteria was inoculated on the film to be evaluated for antibacterial performance, and then a sterilization film (4 cm × 4 cm) was attached. After being placed in a constant temperature and humidity chamber at a temperature of about 35°C and a humidity of more than 90% for 24 hours, the degree of bacterial death was measured. The antibacterial performance was evaluated by comparing the bacterial activity of the test group and the control group, and the results are summarized in Table 3.
[0136] [Table 3]
[0137] category Segmentation Example 5 Example 6 Example 7 Example 8 Comparative Example 3 Comparative Example 4 Antimicrobial staphylococcus 99.999 99.991 99.996 99.994 0 0 Escherichia coli 99.999 99.999 99.999 99.999 0 99.611
[0138] The features, structures, effects, etc. illustrated in the above embodiments may be combined or modified by those skilled in the art in other embodiments. Therefore, the contents related to these combinations and modifications should be interpreted as being included in the scope of the present invention.
[0139] The hard coating composition according to the present invention can be widely used in various applications such as elevators, handles, tables, etc. through coating, and can mainly be used as a coating material suitable for transparent displays.
Claims
1. An antibacterial hard coating composition, characterized in that: include: Silver nanoparticles having a coating layer formed of a polymer on the surface, wherein the content of the silver nanoparticles is 0.02 to 0.2 weight % of the weight of the antibacterial hard coating composition; Adhesive resin; a curing agent for curing the adhesive resin; an organic solvent for dissolving the binder resin and comprising a ketone solvent; and A basic dispersant for dispersing the silver nanoparticles.
2. The hard coating composition according to claim 1, characterized in that: The hard coating composition has an antibacterial property of more than 99.9% against Staphylococcus aureus and Escherichia coli after curing.
3. The hard coating composition according to claim 2, characterized in that: The alkaline dispersant is selected from one or more of the group consisting of sodium hydroxide, diethanolamine, triethanolamine, and phosphine ligand substituted substances.
4. The hard coating composition according to claim 3, characterized in that: The alkaline dispersant is contained in an amount of 5 to 20 parts by weight based on 100 parts by weight of the silver nanoparticles.
5. The hard coating composition according to claim 4, characterized in that: The average particle size of the silver nanoparticles is 5 to 50 nanometers.
6. The hard coating composition according to claim 4, characterized in that: The silver nanoparticles are spherical.
7. The hard coating composition according to claim 1, characterized in that: The molecular weight of the capping agent is 10,000 to 360,000.
8. The hard coating composition according to claim 1, characterized in that: The coating layer has a thickness of 0.5 nanometers to 10 nanometers.
9. The hard coating composition according to claim 1, characterized in that: The ketone solvent is methyl ethyl ketone.
10. A method for preparing a hard coating composition, characterized in that: The following steps are involved: Preparation steps of silver nanoparticles: Ag is + Ion reduction forms a coating layer composed of a polymer on its surface to synthesize silver nanoparticles; a dispersion preparation step of mixing the silver nanoparticles with methyl ethyl ketone; The hard coating liquid preparation step is to mix the dispersion liquid with a binder resin and an alkaline dispersant so that the content of the silver nanoparticles is 0.02 to 0.2 weight % of the weight of the hard coating composition.